The mediated politics of place and people: picturing the 'contested place-making' of Irish Travellers at Dale Farm. (4th May 2017) - Roosvall, Anna
ABSTRACT: This article discusses meanings of people–place relationships, relating to ethnicity–class–gender intersections. The case examined concerns the 'contested place-making' of Irish Travellers at Dale Farm (UK), where the Travellers were eventually evicted from a place they owned. The material consists mainly of online slideshows in the Guardian. Visuals and place share the role of concretizing news, situating them and underlining their truth claims. Hence, news visuals are well suited for discussions of relationships between places and peoples. The study comprises theories of media, place and identity, relating to mobility, minorities and globalization. Methodologically, compositional analysis, discourse-theoretical method and an intersectional approach are combined. The place conflict is rarely understood in terms of justice. Instead, ethnicity–class–gender intersections appear as significant in the imagery, countering certain old stereotypes, but also connecting to discourses of 'threatening minorities', and 'bad mobility'. Manifested through excessive imagery of barricades/fences/walls/gates, 'identity management' meets 'place management', detaching some identities from some places. The Travellers thus appear as anomalies, separated from others. This is partly connected to the slideshow format, where linguistic elaboration on motifs is very limited, partly to the selection of certain themes and motifs in the slideshows, and partly to the societal politics surrounding the issue.